THU0563 Prognostic Value of the 2014 Hscore in Adult Hemophagocytic Syndrome: Analysis in 111 Consecutive Patients (Reghem-Geas-Semi Spanish Cohort). (9th June 2015) - Brito Zeron, P.; Moral Moral, P.; Martínez Zapico, A.; Fraile, G.; Fonseca, E.; Pérez Guerrero, P.; Robles, A.; Vaquero Herrero, M.; Ruiz De Temiño, A.; Forner, M.J.; Larrañaga, J.R.; Prieto, S.; et al.
Abstract : Background: HScore is a numeric scoring system recently proposed by Fardet et al in 2014, designed to estimate the risk of having hemophagocytic syndrome (HS) in adults. Objectives: The objective of this study is to analyze the potential use of the HScore as a prognostic factor in a large cohort of Spanish patients with adult HS. Methods: In June 2013, the Study Group of Autoimmune Diseases (GEAS-SEMI) created the National Registry of Adult Patients with HS. Patients were diagnosed according to the fulfillment of the Histiocytosis Society criteria proposed in 1991 and updated in 2004. The HScore includes 9 clinical, laboratory and histopathological criteria, and the score may range from 0 to a maximum of 337 points. Results: By January 2015, the REGHEM registry included 111 adult patients with HS, 65 (59%) men and 46 (41%) women, with a mean age at diagnosis of 49.16 years (range 12-85 years); nineteen patients (17%) were not born in Spain (58% from Latin America, 21% from Africa and 16% from Asia). Tissular hemophagocytosis was confirmed in 97/107 (87%) cases. The main underlying diseases diagnosed before HS were autoimmune/rheumatological diseases in 36 (33%) patients, chronic infections in 24 (22%) and neoplasia in 25 (23%) patients. The great majority of patients required ICU admission and death occurred in 59 (53%). The HScore was retrospectively calculated in 61 patients in whom all the criteria required could be applied: the mean HScore was 230, 03 (range, 58-306). No significant differences for the mean HScore were found with respect to gender, age at diagnosis, underlying diseases, or severe internal organ involvement (pulmonary, renal or central nervous system). However, a higher mean HScore was found in foreign patients (257 vs 222, p=0.02), in patients with concomitant infections with confirmed microbiological isolation (243 vs 214, p=0.022) and in those who required vital support (248 vs 212, p=0.004). Patients who died showed a higher mean HScore in comparison with survivors (241 vs 217, p=0.05). Conclusions: Hemophagocytic syndrome is a life-threatening multisystemic disease that often requires vital support in intensive care units. Despite this and the use of a complex therapeutic approach, half of the patients died. We found higher HScores in patients presenting with a complicated HS (concomitant infections, need for vital support and death). The use of the new HScore as prognostic factor may help to identify patients with a poor outcome. Disclosure of Interest: None declared